Trauma and Racial Minority Immigrants: Turmoil, Uncertainty, and Resistance. 2021
DOI: 10.1037/0000214-013
|View full text |Cite
|
Sign up to set email alerts
|

Coping with trauma: Resilience among immigrants of color in the United States.

Abstract: P eople immigrate for many reasons (e.g., economics and work, family reunification, refuge) that vary in their level of exposure to trauma. In addition to typical stressors of immigration, immigrants of color may face additional challenges given their ethnic minority status (Suárez-Orozco et al., 2012). Various conditions precede immigration for those who come to the United States. This chapter utilizes the model of cumulative racial/ethnic trauma for Americans of Middle Eastern and North African (MENA) descen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Accessing social support within and outside of one’s family and ethnic and/or religious community is thought to help Muslim American emerging adults to cope with discrimination (Awad et al, 2021; Manejwala & Abu-Ras, 2019; Tummala-Narra & Claudius, 2013). However, emerging adults appear to have mixed experiences of seeking support.…”
Section: Social Support Among Muslim Americansmentioning
confidence: 99%
See 1 more Smart Citation
“…Accessing social support within and outside of one’s family and ethnic and/or religious community is thought to help Muslim American emerging adults to cope with discrimination (Awad et al, 2021; Manejwala & Abu-Ras, 2019; Tummala-Narra & Claudius, 2013). However, emerging adults appear to have mixed experiences of seeking support.…”
Section: Social Support Among Muslim Americansmentioning
confidence: 99%
“…Experiences of Islamophobia have been found to have detrimental impacts on mental health and well-being of Muslim, Arab, and South Asian Americans (Abu-Ras & Suárez, 2009; Aprahamian et al, 2011; Awad et al, 2021; Lowe, Tineo, Bonumwezi, & Bailey, 2019; Lowe, Tineo, & Young, 2019; Tummala-Narra, 2021). Still, there is a scarcity of research examining different types and contexts of discrimination and their relationship with mental health symptomology among Muslim American college students.…”
mentioning
confidence: 99%
“…COVID-19 affected all families in the United States, but the disruptions of the pandemic have disproportionately impacted the well-being of families who have historically faced greater adversity, particularly families of color and low-income families. Families of color and low-income families are more likely to work in industries that experienced significant lay-offs and furloughs, and they are more likely to work in industries that require in-person work, consequently increasing risk of COVID-19 exposure and transmission ([ 6 ]; Hardy and Logan 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of COVID-19 have and will continue to unevenly impact Black, Indigenous, and people of color (BIPOC) and low-income households, research on resilience has found that the more experience people have with prior disasters or adversities, the more they are prepared and able to navigate systems during future struggles [ 8 ]. Indeed, some studies have found high resilience in families of color in the wake of COVID-19 and other traumatic events [ 6 , 9 ]. Researchers have also found that low-income families are resilient in numerous ways and able to solve problems when they arise [ 10 ].…”
Section: Introductionmentioning
confidence: 99%